Aa from lomas formations. A new Orchidaceae record from the desert coast of Peru - Trujillo, Delsy (2011)
Orchid species of the genus Aa have been described as mostly restricted to high elevations zones in the Andes and mountains of Costa Rica. Here, we record populations of Aa weddelliana at lower elevations in lomas formations from the desert coast of Peru; this is the fourth species of Orchidaceae registered in Peruvian lomas. Furthermore, we illustrate and discuss some floral features of Aa weddelliana.